Potential common targets of music therapy intervention in neuropsychiatric disorders: the prefrontal cortex-hippocampus -amygdala circuit (a review) - Dan, Yuqin; Xiong, Ying; Xu, Danghan; Wang, Yuqi; Yin, Meng; Sun, Pengwei; Ding, Yi; Feng, Ziyun; Sun, Peng; Xia, Weili; Yu, Gongchang; Li, Li (Frontiers in Human Neuroscience, 2025)
As life becomes more stressful, neurological disorders, psychiatric disorders, and comorbidities of the two are becoming more and more of a concern. Multiple neuropsychiatric disorders share the same mental and somatic dysfunction and may involve common brain circuits and mechanistic targets. Music therapy, as an art form with proven efficacy, low cost and few side effects, is promoted for use in interventions for neuropsychiatric disorders. This may be closely related to the release of signaling molecules such as monoamine neurotransmitters, the glutamatergic system, the gut-microbiota-brain axis, pro-inflammatory cytokines and the endogenous opioid peptide system. However, fewer studies have mentioned the main targets of music to promote functional changes in brain regions. Therefore, this paper is a review of the mechanisms by which music therapy interacts with the prefrontal cortex-hippocampus-amygdala circuit through the aforementioned molecules. It is also hypothesized that glial cells, mitochondria and microRNAs are microscopic targets for musical intervention in neuropsychiatric disorders. The aim is to give new ideas for future research into the biological mechanisms of music therapy intervention in neuropsychiatric disorders.